2018 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2018
DOI: 10.1109/iros.2018.8594442
|View full text |Cite
|
Sign up to set email alerts
|

Approximate Distributed Spatiotemporal Topic Models for Multi-Robot Terrain Characterization

Abstract: Unsupervised learning techniques, such as Bayesian topic models, are capable of discovering latent structure directly from raw data. These unsupervised models can endow robots with the ability to learn from their observations without human supervision, and then use the learned models for tasks such as autonomous exploration, adaptive sampling, or surveillance. This paper extends single-robot topic models to the domain of multiple robots. The main difficulty of this extension lies in achieving and maintaining g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…While there has been progress in other unsupervised semantic image segmentation approaches [21], including deeplearning based methods [22], by not leveraging these correlations they produce lower quality maps of large environments. Doherty et al [23] showed that repeatedly matching the topic models of two robots with the Hungarian algorithm [24], merging them together, and distributing the merged model would result in both robots converging to a single set of good semantic labels, even if this was done at a low frequency. To our knowledge, [23] is the only prior work that has explored multi-robot distributed semantic mapping with representations learned online.…”
Section: Related Workmentioning
confidence: 99%
“…While there has been progress in other unsupervised semantic image segmentation approaches [21], including deeplearning based methods [22], by not leveraging these correlations they produce lower quality maps of large environments. Doherty et al [23] showed that repeatedly matching the topic models of two robots with the Hungarian algorithm [24], merging them together, and distributing the merged model would result in both robots converging to a single set of good semantic labels, even if this was done at a low frequency. To our knowledge, [23] is the only prior work that has explored multi-robot distributed semantic mapping with representations learned online.…”
Section: Related Workmentioning
confidence: 99%
“…Thus, the robots are likely to use a variety of distinct semantic labels to represent the same phenomenon, especially if there are many different phonomena in the environment. Some previous work which started to address this issue explored sharing the topic-word distribution matrices between robots regularly, thus ensuring that all robots would eventually converge towards shared semantic representations [23].…”
Section: Multi-robot Federated Explorationmentioning
confidence: 99%
“…This enables the robots to communicate labels and observations among each other, and potentially still merge topic models if appropriate, with fewer drawbacks and less communication required. Of particular interest is using the CLEAR algorithm [33], which is capable of efficiently solving the multi-agent data association problem to find all sets of equivalent semantic labels across all robots, to find much better correspondences than the 1-to-1 correspondences solved using the Hungarian algorithm in [23].…”
Section: Multi-robot Federated Explorationmentioning
confidence: 99%
“…For example, the recovery of soundtraps for biological research in Figure 1-3, and the dangerous task of inspecting ship hulls for mines (which has previously been performed by either trained human divers or marine mammals). Additionally, there has been increasing interest in the use of robots for semantic-level biological surveying, as in prior work which examines online learning for multiple communication-constrained underwater vehicles [12].…”
Section: Motivationmentioning
confidence: 99%